Member Adherence to a Health Insurer-Sponsored Gap Closure Program Using Multi-Target Stool DNA Test for Colorectal Cancer Screening - Mallik Greene; Timo Pew; Quang Le; Alisdair Philp; William K. Johnson; A. Burak Ozbay; John Kisiel; Michael Dore; Derek Ebner; A. Mark Fendrick; Paul Limburg (Journal of Primary Care & Community Health, 2024)
Objectives: To describe member adherence to a mail-based, health insurer-sponsored gap closure program for colorectal cancer (CRC) screening using multi-target stool DNA (mt-sDNA; Cologuard ® ) tests. Methods: Combined patient data from Exact Sciences Laboratories LLC and data from mass-mailed mt-sDNA orders placed by a large Medicare Advantage Insurance Plan were analyzed (03/01/2023-06/30/2023). Adherence and time to test return were the primary and secondary outcomes, respectively. Their association with patient characteristics was evaluated using multivariable regression. Results: Among the 3201 member-patients included (86.6% aged 65-75 years; 58.7% female), adherence rate was 49.4%, and mean time to test return was 25.5 days. After multivariable adjustment, the odds of test return were significantly higher among 65- to 75-year-olds (odds ratio [OR] = 1.59 relative to 45- to 64-year-olds), those living in small towns (OR = 1.43 relative to metropolitan-located individuals), and with digital outreach via both SMS and email (OR = 4.31 relative to no digital outreach). Time to test return was shorter in 65- to 75-year-olds than in 45- to 64-year-olds and was not associated with other patient characteristics. Conclusions: Mass-mailed mt-sDNA tests for CRC screening were associated with an overall adherence rate of about 50% in this Medicare Advantage population, with higher likelihood of test return among patients receiving digital outreach.